1988
DOI: 10.1016/s0022-5347(17)42074-x
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase-Type Plasminogen Activator as a Marker for the Formation of Distant Metastases in Prostatic Carcinomas

Abstract: Plasma levels of urokinase-type plasminogen activator have been investigated in 80 patients with prostatic carcinoma by means of a radioimmunoassay. A total of 30 patients with disseminated prostatic carcinoma had significantly elevated levels of urokinase-type plasminogen activator, whereas the plasma levels in patients without metastases did not differ from a healthy age matched control group. Sensitivity of elevated urokinase-type plasminogen activator levels in patients with prostatic carcinoma for the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 10 publications
4
41
0
Order By: Relevance
“…This cascade is an essential step for malignant cell transport. Growth factors including bFGF and activated ERK1/2 have been shown to promote uPA production in various tumoral and normal cell types (32)(33)(34)(35). Elevated levels of uPA are found in patients with advanced stages of prostate cancer and it is a strong indicator of poor prognosis (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cascade is an essential step for malignant cell transport. Growth factors including bFGF and activated ERK1/2 have been shown to promote uPA production in various tumoral and normal cell types (32)(33)(34)(35). Elevated levels of uPA are found in patients with advanced stages of prostate cancer and it is a strong indicator of poor prognosis (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmin, in turn promotes cancer metastasis by breaking down the extracellular matrix, including fibronectin and laminin (32,33). Notably, the malignant phenotype of prostatic tumor cells correlates with high expression of both uPA and its receptor (uPAR), and plasma uPA has been identified as a biomarker for prostate cancer progression in Dunning rats and prostate cancer patients (34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated circulating levels of uPA and uPAR have been linked to PCa stage and bone metastases. [68][69][70] In these studies, preoperative plasma uPA was a strong predictor of biochemical recurrence after surgery. Both preoperative uPA and uPAR were associated with features of aggressive biochemical recurrence such as development of distant metastasis suggesting an association with occult metastatic disease at time of local therapy.…”
Section: Urokinase Plasminogen Activation Systemmentioning
confidence: 95%
“…Plg activators, uPAR, and PAI, are all excellent prognostic markers in human cancer, further implicating the PA system in tumor progression (Andreasen et al, 1997b(Andreasen et al, , 2000. Thus, extensive epidemiological studies have revealed that high expression of Plg activator, uPAR, or PAI-1 in human breast (Duffy et al, 1990;Foekens et al, 1992;GrondahlHansen et al, 1993), colorectal (Ganesh et al, 1994a,b), lung (Oka et al, 1991;Pedersen et al, 1994), prostate (Hienert et al, 1988), and gastric cancer (Heiss et al, 1995;Nekarda et al, 1994), is associated with a poor prognosis. The direct causal relationship between Plg activator expression and tumor progression was furthermore demonstrated in a number of studies using the chick chorio-allantoic membrane metastasis model, and the mouse spontaneous and experimental metastasis models.…”
Section: Introductionmentioning
confidence: 99%